2021
DOI: 10.1021/acs.energyfuels.1c03471
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Fracture Conductivity in Various Carbonate Rocks Treated with GLDA Chelating Agent and HCl Acid

Abstract: Acid fracturing is applied to increase the productivity of carbonate formations. The acid creates rough fracture surfaces and channels that keep the fractures open after closure. This study investigated a chelating agent and HCl acid as acid fracturing fluids in three different carbonates: Austin chalk, Indiana limestone, and Silurian dolomite. The impact of rock hardness and surface roughness on conductivity was thoroughly studied. We collected six core samples, two from each type, with 1.5-in. × 6-in. dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Organic compounds with two or more groups (ligands) that can donate electrons to capture or adsorb the positively charged ions (metal ions) are named chelating agents. A variety of chelating agents are utilized within the petroleum industry and in diverse engineering and manufacturing fields. , Their application in the petroleum industry mainly involves acidizing, hydraulic fracturing, prevention of scale formation, scale removal, filter cake removal, and enhanced oil recovery (EOR). Inorganic acids are occasionally employed for stimulation and scale removal. Many other factors contribute to their utility, such as hydrogen sulfide (H 2 S) and corrosion, resulting in higher operating costs.…”
Section: Introductionmentioning
confidence: 99%
“…Organic compounds with two or more groups (ligands) that can donate electrons to capture or adsorb the positively charged ions (metal ions) are named chelating agents. A variety of chelating agents are utilized within the petroleum industry and in diverse engineering and manufacturing fields. , Their application in the petroleum industry mainly involves acidizing, hydraulic fracturing, prevention of scale formation, scale removal, filter cake removal, and enhanced oil recovery (EOR). Inorganic acids are occasionally employed for stimulation and scale removal. Many other factors contribute to their utility, such as hydrogen sulfide (H 2 S) and corrosion, resulting in higher operating costs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the current research on the acid rock reaction behavior of carbonate reservoir. There are a large number of studies, both on-site acid rock jet experiment and indoor experimental research, such as acid rock reaction law, optimization of conventional acid system, synthesis of surfactants. , However, there are few studies on the true acid system of a carbonate reservoir. Especially under the background of increasing exploration and development of carbonate reservoirs in China, the study of the autogenous acid system should be accelerated.…”
Section: Introductionmentioning
confidence: 99%
“…The conductivity of created fractures is maintained by the injection of a so-called proppant (solid material, usually sand) or, more naturally, by asperities, which result from the reaction between an acid (usually HCl) and reservoir rock . The extraction of hydrocarbons results in increased stresses on the fracture surface, which, combined with the elevated temperatures, causes gradual plastic deformation of the reservoir rock (rock creeping). , Creeping, in turn, leads to reduction of the fracture width (conductivity reduction), presented in terms of a failure of asperities and embedment (indentation) of proppant into formation rock. Researches have shown that the mechanical characteristics of the reservoir rock (hardness, Young’s modulus), fracture surface roughness, proppant properties (type, size, concentration), and acid properties (type, reaction time) are critical factors that affect the decline of the fracture conductivity. , Moreover, Aljawad et al validated through modeling the carbonate formation that hardening of the fracture surface improves sustenance of its conductivity and the well’s productivity . On the basis of this, strengthening carbonate reservoir rocks can mitigate the effect of the above-mentioned problems and provide long-term sustenance of the fracture conductivity in carbonate formations. , However, practical application records of chemical rock strengthening techniques in carbonate reservoirs, including hydraulic/acid fracturing operations, are still absent.…”
Section: Introductionmentioning
confidence: 99%